The value of routine radiography in patients with knee osteoarthritis consulting primary health care: A study of agreement. (March 2014) - Skou, Søren T.; Thomsen, Hanne; Simonsen, Ole H.
Abstract Background: Radiography is often used routinely by the general practitioner (GP) in knee osteoarthritis (KOA), even though the diagnosis can be made based on clinical findings. However, radiography may also be requested when serious pathology is suspected. The agreement between the radiographic and the GPs clinical diagnosis and the ability of radiography to rule out serious pathology in clinical KOA is unknown, despite that this is important to evaluate the clinical value of radiography. Objectives: The objectives were to evaluate agreement between the radiographic and clinical diagnosis in KOA; and to describe radiographic features in patients referred from their GP with clinical KOA. Methods: Referral forms from GPs and radiographs of 1 334 consecutive patients above 40 years not previously diagnosed with KOA were evaluated. The agreement between primary indication for radiographic referral (± clinical KOA; according to the recommendations from the European League Against Rheumatism) and the radiographic diagnosis (± radiographic KOA; Kellgren and Lawrence score ≥ 1) was estimated using Cohen's Κ statistics. Furthermore, an evaluation of radiographic features was carried out in patients with clinical KOA (n = 997). Results: The strength of the agreement was 0.106 to 0.298 with the lowest agreement in the youngest patients and the highest in the oldest patients. Five radiographs (0.5%) revealed conditions needing further investigation or specific treatment (osteonecrosis, osteochondral lesion, fracture and subluxation). Conclusion: In patients with clinical KOA, the radiography seems only indicated if the clinical assessment cannot rule out other diagnoses or serious pathology.